Neurotrauma and Cerebrospinal Fluid in Homer's Poems - Borroto, Carlos Enrique Hernández; Hernández, Orquidia Reyes de; Plana, Yuri Medrano (Indian Journal of Neurotrauma, 2024)
Homer's Iliad, from the 8th century BC, remains the oldest record of Greek medicine and a unique source of surgical history. The Odyssey, also authored by Homer, narrates several medically significant events. Among the 148 war traumas described in the Iliad, over a quarter occurred in the craniocervical region. Studies on the Odyssey report at least 11 craniocervical traumas, 9 of which prove fatal. Is there any indication of the presence of cerebrospinal fluid (CSF) in the cases described by Homer, considering its last mention was 800 years prior in the Egyptian surgical papyrus of Edwin Smith? A passage in the Iliad suggests that the “tears” Homer mentions in the eyes of Eumelos, resulting from trauma, might be due to CSF oculorrhea secondary to a skull base fracture. In Odyssey Book IX, when the Cyclops strikes the heads of two sailors, and fluid and cranial contents emerge, it can be inferred that the poet was aware of fluid in the head (CSF), as there is no mention of blood. It is proposed that 800 years after the writing of the Edwin Smith papyrus, Homer probably provides the second human observation of CSF associated with traumatic situations involving direct head blows.
Keywords: cerebrospinal fluid; Edwin Smith papyrus; Homer; Iliad; Odyssey